The Concept of Income and Income Recognition in the Context of Personal Taxation: Theoretical Background and Practical Problems - Montvidas, Martynas (Teisė, 2024)
This article analyses doctrinal grounds for the definition of income, problems related to the recognition of income, as well as the related legal regulation and its application in case law.
Keywords: Personal Income Tax; Income; Recognition of Income; Accretion to Economic Power